Diatomic Pd−Cu Metal‐Phosphorus Sites for Complete N≡N Bond Formation in Photoelectrochemical Nitrate Reduction. (19th September 2022) - Sun, Jie; Yang, Hanxue; Gao, Weiqi; Cao, Tongcheng; Zhao, Guohua
Abstract: The synergistic effect of bimetallic heterogeneous catalysis in the reaction of nitrate reduction to nitrogen has been widely discussed, but it is still not clear how this effect works at the atomic scale, hindering the rational design of high‐performance catalysts. Here, for the first time, 2D phosphorene was used as a giant P ligand to confine high‐density PdCu dual‐atom to form a unique PdCuP4 coordination structure, and this catalyst achieves 96.3 % NO3 − removal rate and 95.2 % N2 selectivity. In situ characterization combined with density functional theory (DFT) calculations show that the PdCu dual‐atom form covalent‐like bonds with adjacent P atoms, reducing the adsorption energy of the reactants. The synergistic effect of PdCu dual‐atom promotes the breaking of N−O bond, and the short bond length of ≈3 Å between PdCu atoms accelerates the transfer of NO2 −, and eventually the two Pd−N adjacent to the surface of Pd rapidly combine to form N2 . Abstract : An in situ photoreduction strategy is taken to synthesize diatomic Pd−Cu catalysts on 2D phosphorene. Owing to the strength of the unique synergistic effect of PdCuP4 coordination, the adsorption of NO3 −, the transfer of intermediates, and the formation of N≡N bond are all enhanced, leading to a high NO3 − removal rate and N2 selectivity.